Utilization of sago (Metroxylon sagu Rottb.) flour as the major ingredient in processing pre-baked pie crust - Balaba, Rocky Jay Badilla (2010)
This product development study was done to develop a low-cost product which is pre-baked pie crust utilizing a local raw material. sago (Metroxylon sagu Rottb.) flour. The product was prepared by substituting sago flour to wheat flour in 50:50, 75:25 and 10:0 proportions. The three formulations were then subjected to Preference Ranking Test and results showed that they are not significantly different form each other using the Friedman's Test. However, the product with 75% sago flour was selected as the final product based on the ease of preparation and higher sago flour content. The 100% sago-substituted pie crust resulted to a gluten-free product which is flaky and hardly formed a dough during processing. On the other hand, the sago flour was not totally maximized in the formulation with 50% sago flour. The final product which has an estimated cost of Php40.30% per crust was further subjected to Consumer Acceptability test using the 9-point Hedonic scale and the responses were analyzed by measuring the mode. Results showed that the panelists liked the product's appearance, texture and overall quality very much while they extremely liked its flavor and aftertaste. Based on the proximate analysis conducted, the product has 71.87% carbohydrates, 22.12% fat, 3.08% ash, 1.47% moisture content, 1.46% protein and 1.04% fiber.